Implementasi Teknologi Converter Bahasa Isyarat Indonesia dalam Membangun Komunikasi antara Siswa Berkebutuhan Khusus dengan Guru di SMK BPP Veteran Bandung - Zulkarnaen; Andriana; Rahman, Sutisna Abdul; Rohmah, Dede Siti; Turesna, Ganjar; Nurdiansyah, Sansan (Lembaga Pengabdian kepada Masyarakat Universitas Langlangbuana, 2024)
Effective communication between special needs students (SNS) and teachers is one of the biggest challenges in inclusive education, particularly at vocational high schools (SMK). SMK BPP Veteran Bandung, as an institution that implements inclusive education, faces this challenge in its effort to provide equal education for all students. This community service program aims to implement Indonesian Sign Language Converter technology to assist communication between SNS and teachers. The technology is designed to translate Indonesian Sign Language into text and voice, and vice versa, enabling SNS to communicate more effectively with their teachers. The program began with a needs analysis through observations and interviews, followed by teacher training to use the technology, and then implementation and evaluation in classrooms. The results of this program show a significant improvement in SNS engagement in learning and enhanced communication quality between SNS and teachers. This program is expected to be adopted more broadly in other schools that implement inclusive education.